Konsep Pembebasan dalam Ajaran Paulus dan Implikasinya terhadap Perbudakan - Prading, Friskilia Randa (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2025)
This literature review aims to analyze the Concept of Liberation in the Teaching of Paul and its implications for slavery in the social and theological context. The primary focus of this research is on Paul’s letters in the New Testament that discuss the concept of liberation, especially as expressed in the letters to the Galatians, Romans, and Philemon. The literature review analysis is conducted to understand how Paul constructs his thoughts on liberation as a result of the grace of Christ and how this concept influences the early church’s views on slavery. This research utilizes methods of analyzing biblical texts, systematic theology, and the historical-cultural context of Paul’s era. The research findings are expected to illustrate how Paul’s teachings on liberation provide a theological foundation for the early church’s perspectives on slavery and whether this understanding is reflected in their social actions. The implications of Paul’s concept of liberation on slavery can provide profound insights into the early church’s role in responding to complex social issues. This research is expected to contribute to a richer understanding of Paul’s theological contributions to Christian ethics and the struggle against inequality